Developing a standardized approach to prevention and outpatient management of febrile neutropenia. Issue 28 (1st October 2022) - Crespo, Andrea; Gallo-Hershberg, Daniela; Enright, Katherine; Forbes, Leta Marie; Vu, Kathy
Abstract : 234 Background: Optimal prevention and safe management of febrile neutropenia (FN) in the outpatient setting, when clinically appropriate, can help to keep vulnerable patients from experiencing severe complications requiring hospitalization. Variation in the prevention and outpatient management of FN was identified as a quality and safety gap by Ontario clinicians. This initiative aimed to facilitate a standardized approach to prevention and outpatient management of FN through the development of practical, evidence-based health-care provider and patient resources. Methods: A clinical practice guideline was developed by a 15-member multidisciplinary Working Group (WG) consisting of physicians, pharmacists, nurses, and administrators who are knowledgeable in the areas of prevention and management of FN. The WG reviewed current relevant international guidelines and available literature on primary and secondary FN prophylaxis and FN management, with an emphasis on the optimal use of granulocyte colony-stimulating factor (G-CSF) and appropriate FN management in the outpatient setting. The 2016 Cancer Care Ontario recommendations on the use of G-CSF were used as a foundation for the prevention of FN content. Key clinical questions were identified by the WG, and content was approached with an Ontario-specific lens. Recommendations were developed using an iterative consensus-building process over six WG meetings. The guideline report was reviewed by external clinical experts who validated final content. Accompanying patient information was informed by health literacy best practices, existing symptom management resources, and input from patient education experts, patients, and caregivers. Results: A user-friendly clinical practice guideline was created. Definitions, risk factors, FN prophylaxis strategies based on risk/treatment intent, and appropriate outpatient management of FN are described. Key clinical questions are reviewed and a total of 25 evidence-informed consensus-based recommendations are presented. The guideline includes FN risk assessment and outpatient FN management algorithms, as well as summaries of available literature and WG discussion. The accompanying patient information explains what neutropenia and neutropenic fever are, lists potential symptoms, and describes management strategies in patient-friendly language. All resources are publicly available on the Ontario Health-Cancer Care Ontario website and have been disseminated broadly to relevant stakeholders via email, social media, and webinars. Conclusions: Review of current evidence and expertise from oncology and infectious disease clinicians resulted in an evidence-informed, consensus-based guideline. This clinical practice guideline and accompanying patient information resource can help to facilitate safe, standardized prevention and appropriate outpatient management of FN.